A novel cell-based assay for the evaluation of immune- and inflammatory-related gene expression as biomarkers for the risk assessment of drug-induced liver injury. (22nd January 2016) - Oda, Shingo; Matsuo, Kentaro; Nakajima, Akira; Yokoi, Tsuyoshi
Highlights: Drug-induced liver injury (DILI) is a major safety problem in drug development. A novel cell-based assay was developed based on immune and inflammatory factors and drug metabolism to detect drugs with a propensity to cause DILI. The IL-1β, IL-8, and S100A9 mRNA levels were acceptable indicators for the risk assessment of DILI. An integrated score of the three factors showed a superior discriminative ability. Our method considering immune and inflammatory factors and drug metabolism is useful for detecting DILI-positive drugs. Abstract: Drug-induced liver injury (DILI) is a major problem in drug development. Although some in vitro methods assessing DILI risk that utilize hepatic cell death or cellular stress as markers have been developed, the predictive ability of these tests is low. In this study, we sought to develop a novel cell-based assay for the risk assessment of DILI that considers drug metabolism as well as immune- and inflammatory-related gene expression. To accomplish this goal, human hepatoma HepaRG or HepG2 cells were treated with 96 drugs with different clinical DILI risks. The conditioned media were subsequently used to treat human promyelocytic leukemia HL-60 cells, and the mRNA expression levels of immune- and inflammatory-related genes in the cells were measured. An area under the receiver operating characteristic curve (ROC–AUC) was calculated to evaluate the predictive performance of the mRNA levels as markers to discriminate DILI risk. The expression of interleukin-8 (IL-8) in HL-60 cells treated with conditioned media from HepaRG cells (HL-60/HepaRG) exhibited the highest ROC–AUC value of 0.758, followed by the expression of IL-1β in HL-60/HepaRG (ROC–AUC: 0.726). Notably, the ROC–AUC values of these genes were higher in HL-60/HepaRG than in HL-60/HepG2, which suggests that HL-60/HepaRG has a higher potential for detecting the metabolic activation of drugs. An integrated score calculated from the levels of S100 calcium-binding protein A9 (S100A9), IL-1β, and IL-8 more precisely determined the DILI risks than individual gene expression did. The developed cell-based assay that utilizes immune-related gene expression would aid in the assessment of potential DILI risks.